Social Audit in the Theoretical Field of Social Responsibility - Ahaverdiieva Khalida F.; Ivanisov Oleg V.; Ivanisov Oleg V. (Bìznes Inform, 2019)
The aim of this work is to justify the need for conducting social audits in domestic enterprises. The relevance and necessity of conducting social audits in the context of corporate social responsibility is substantiated. The theoretical justification of the concept “social audit” is investigated. Features of conducting social audit in certain subsystems of the social and labor sphere are summarized with consideration for peculiarities of foreign experience. Prospects for further research at the level of analysis is studying the features of organization of social audits at implementing business activities by modern enterprises. In respect of the applied aspect, the specific mechanisms and technologies of social audit still remain insufficiently studied.